Effects of indium doping on the structural and optical properties of CdSe thin films deposited by chemical bath - Pérez González, A.M.; Arreola, I.V.; Tepantlán, C.S. (Revista Mexicana de Física, 2009)
Thin films of n-type CdSe have been grown on Corning glass substrate by chemical bath deposition, prepared with Sodium Seleno-Sulphate (Na_2SSeO_3), Cadmium Chloride (CdCl_2) and Indium Tri-Chloride (InCl_3), mixed in an aqueous environment. The effects of different In doping concentrations have been investigated. X-ray diffraction spectra show that at low In concentration only the CdSe lattice is present in the deposited film, whereas CdIn_2Se_4 and InSe compounds are obtained at higher In concentrations. Optical properties have been calculated from transmission spectra and photoluminescence measurements. From transmission spectra, the absorption coefficient and optical gap were obtained; photoluminescence spectra show band-band recombination from 10 K to room temperature.